Emerging Diseases in Spain Strawberry Crops: Neopestalotiopsis Leaf and Crown Rot and Fusarium Wilt - Manuel Avilés; Ana M. Pastrana; Celia Borrero (Plants)
In recent years, strawberry cultivation in Spain has been increasingly affected by new and re-emerging fungal diseases. The most significant emerging diseases in Spain include those caused by Neopestalotiopsis spp. Maharachch., K.D.Hyde & Crous and Fusarium oxysporum f. sp. fragariae Winks & Y.N. Williams. These pathogens are difficult to control due to their pathogenic variability (presence of pathotypes and/or races), the lack of knowledge about the susceptibility of the different cultivars, the limited availability of effective fumigants, and the absence of sufficient information about their sources of inoculum. Both pathogens can cause root and crown rot, leading to plant collapse and significant losses for strawberry producers. Several factors have contributed to the rise of these diseases in Spain: (i) the gradual ban on key soil fumigants has left the crop vulnerable; (ii) there has been a notable diversification in the origin of mother plants used in cultivation, with plants now sourced from various countries, increasing the risk of long-distance pathogen spread; (iii) the introduction of numerous new strawberry varieties, which exposes more genotypes to pathogenic infections; and (iv) changes in planting times, leading to younger and more vulnerable plants being exposed to heat stress, as well as an increase in disease susceptibility. Neopestalotiopsis spp. and Fusarium oxysporum f. sp. fragariae have also become major threats to strawberry crops worldwide, spreading through nursery plants and the movement of plant material. The latest research findings in Spain on both pathogens are highlighted in this manuscript.